Moderate sedation by total intravenous remimazolam-alfentanil vs. propofol-alfentanil for third molar extraction: A prospective randomized controlled trial - Zhao, Nan; Zeng, Jie; Fan, Lin; Wang, Jing; Zhang, Chao; Zou, SiHai; Zhang, Bi; Li, Kai; Yu, Cong (Frontiers in Medicine, 2022)
Abstract: This study aimed to investigate the efficacy and safety of moderate sedation by remimazolam with alfentanil versus propofol with alfentanil in third molar extraction.This single-center, randomized, double-blind clinical trial included 100 adults who underwent third molar ambulatory extraction.All patients had continuous infusion of Alfentanil 0.2mg/kg/min. Group remimazolam with alfentanil (group RA)had an induction dose of 0.08 mg/kg and maintenance dosage of 0.2mg/kg/min. In group propofol with alfentanil (PA group), propofol was infused at an initial concentration of 1.8μg/mL under target controlled infusion(TCI) mode and a maintenance concentration of 1.5μg/mL. The incidence rates of adverse effects were recorded and compared.Depth of sedation was assessed using the modified observer alertness/sedation assessment (MOAA/S) and entropy index. Recovery characteristics were recorded and complications observed for next 24h.The incident of adverse events 5(10%) in the group RA was lower than the group PA 21(42%) (Mean difference 0.153 [95%CI, 0.052-0.452]; P<0.05), with no serious adverse events during the sedation procedure. The incidence of injection pain in group RA was significantly lower than that in group PA (4% VS 26%, mean difference 0.119 [95%CI, 0.025–0.558]; P = 0.004). Before starting local anesthesia, the mean arterial pressure, heart rate, and respiratory rate of the PA group were lower than those of the RA group. None of the patients required further treatments for a decreased heart rate, blood pressure, or low SpO2. The rate of moderate sedation success was 100% in both groups. The MOAA/S score was similar between the groups indicating that the depth of sedation was effective. Group RA had significantly shorter recovery and discharge times than those of group PA.Remimazolam with alfentanil is a safer and more effective alternative for ambulatory sedation and can reduce recovery and discharge time and the incidence of perioperative adverse events compare with propofol.